PENGARUH GAYA MENGAJAR TERHADAP HASIL BELAJAR SOSIOLOGI KELAS XI IIS SMA KEMALA BHAYANGKARI - Satibi, Sarah Berlinggi; Bahari, Yohanes; Stella Prancisca, Stella (Universitas Tanjungpura, 2024)
This research aims to analyze (1) the teaching style of teachers in class XI sociology learning at Kemala Bhayangkari High School. (2) student learning outcomes in class XI sociology learning at Kemala Bhayangkari High School. (3) the influence of the teacher